2014
DOI: 10.1038/aps.2013.187
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 protects mouse podocytes from aldosterone-induced injury in vitro

Abstract: Aim: Aldosterone is elevated in many diseases such as hypertension, diabetic nephropathy and chronic kidney disease, etc. The aim of this study was to investigate the effects of aldosterone on intracellular ROS production and autophagy in podocytes in vitro, and to explore the possibility of ginsenoside Rg1 (Rg1) being used for protecting podocytes from aldosterone-induced injury. Methods: MPC5 mouse podocyte cells were tested. Autophagosome and autophagic vacuole formation were examined under confocal microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Consistent with a recent study, 42 our data showed that autophagy was activated in podocytes by aldosterone. Previous studies have highlighted the essential role of Signaling pathway in podocyte injury Y Yuan et al autophagy for the cellular homeostasis of podocytes in health and disease.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with a recent study, 42 our data showed that autophagy was activated in podocytes by aldosterone. Previous studies have highlighted the essential role of Signaling pathway in podocyte injury Y Yuan et al autophagy for the cellular homeostasis of podocytes in health and disease.…”
Section: Discussionsupporting
confidence: 93%
“…The regulation of autophagy has been thought to be a major mechanism underlying numerous interventions for DN. In podocyte, aldosterone plays a pathogenic role in renal injury under conditions of DN, and aldosterone-treated mouse podocytes showed significantly increased the conversion of LC3-I to LC3-II, Beclin1 expression, indicating altered autophagy status (Mao et al, 2014). Maintenance of autophagy in podocytes was also suggested to be the mechanism by which histone deacetylase 4 inhibition ameliorates podocyte injury and attenuates glomerulopathy in DN .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, maintaining the homeostasis of autophagy may be a mechanism of reducing renal injury. Moreover, Rg1 was found to inhibit the abnormal autophagy induced by aldosterone in rat renal tubular NRK‐52E cells and mouse podocytes, as well as angiotensin II in mouse podocytes, which may contribute to the alleviation of renal injury.…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%